Orden público, policía y vigilancia en la península ibérica, 1867-1926 - Castillo Cañiz, Assumpta; Vaquero Martínez, Sergio (Historia y Política, 2025)
Orden público, policía y vigilancia en la península ibérica, 1867-1926